TYPOLOGY OF THE ROMANIAN RURAL AREA BASED ON THE MODERNIZATION AND RURAL SOCIO-ECONOMIC DEVELOPMENT PERSPECTIVES - Lorena CHIȚEA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The main purpose of this paper is to create a typology of the Romanian rural area according to the stage of socio-economic development, by building an aggregate development index. The research methodology combines multivariate statistical analysis, cluster analysis and GIS territorial mapping. The aggregate development index was built as a weighted sum of 13 indicators, grouped into 3 dimensions: demographic, social and economic. The weight of each dimension and indicator within dimensions was calculated using principal component analysis. The results show that Romania has significant territorial disparities in terms of rural development, with the most developed rural areas being located in the counties around Bucharest, in the west and northwest of the country, while the least developed rural areas are located in the northeast, east and south of the country.